ISOLATION AND PHENOTIPICAL CHARACTERIZATION OF STAPHYLOCOCCUS AUREUS ISOLATED FROM SLAUGHTERED HOUSE WASTE AND CARCASS OF CHICKEN - -, Khusnan; Isrina Oktavia Salasia, Siti; -, Sugiyono (Jurnal Veteriner; Vol 9 No 1 (2008), 2008)
Staphylococcus aureus is known as a potential agent that cause food poisoning. Chicken meats could be as vehicles of food poisoning cases while they contaminated by agents during slaughtered and meat processing as well as infected chickens by S. aureus itself. The aims of the research were to isolated and characterized of S. aureus from liquid wastes of chicken slaughtered house and washing water of chicken carcass. The characterization of S aureus based on mannitol salt agar (MSA), catalase and coagulation assay, production of hemolysins, hydrophobicity test, and the reaction of hemaglutination. Thirty seven samples used in this study were collected from 16 liquid wastes slaughtered chicken house and 21 samples from washing water of chicken carcasses.The research resulted 18 S. aureus isolated from liquid wastes slaughtered house (4 isolates) and from wahing water of chicken carcasses (14 isolates). All 18 isolates fermented mannitol, catalase and coagulase positive, contain of hydrophilic surfaces. Among 18 S. aureus isolates could agglutinate of rabbit erythrocytes for 55%, produced ?-hemolysis (12%) and ?-hemolysis (88%).
Keywords: Staphylococcus aureus, liquid waste slaughtered house, washing water chicken carcass